An Exploration of Gay Adolescents' Self-Concept in Terms of Subjective Well-Being and Social Support - Alfeisyahri Fahlefi, Muhammad; Virgonita I.W, Mulya; Erlangga, Erwin (Psikostudia : Jurnal Psikologi, 2025)
The issue of homosexuality, particularly gay individuals, had been a topic of debate from various perspectives, including both pro and con views. In recent decades, the presence of gay individuals began to gain attention, especially through media and films. This research aimed to explore the relationship between self-concept, subjective well-being, and social support among gay adolescents in Samarinda, as well as analyze the role of social support in moderating or mediating the relationship between self-concept and subjective well-being. This study was quantitative research with a non-experimental approach. There was a significant relationship between self-concept and subjective well-being among gay adolescents in Samarinda, and social support also influenced subjective well-being. The implications of this research could provide insights for policy counseling and more targeted interventions to improve the well-being of gay adolescents through the development of better self-concept and social support. Isu homoseksualitas khususnya gay telah menjadi topik perdebatan dari berbagai sudut pandang termasuk pro dan kontra. Dalam beberapa dekade terakhir keberadaan gay mulai mendapatkan perhatian terutama melalui media dan perfilman. Penelitian ini bertujuan untuk menelusuri hubungan antara konsep diri, subjective well-being, dan dukungan sosial pada remaja gay di Samarinda, serta menganalisis peran dukungan sosial dalam memoderasi atau memediasi hubungan antara konsep diri dan subjective well-being. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan non-eksperimental. Terdapat hubungan yang signifikan antara konsep diri dan subjective well-being pada remaja Gay di kota Samarinda serta dukungan sosial yang turut mempengaruhi subjective well-being. Implikasi dari penelitian ini dapat memberikan wawasan bagi penyuluhan kebijakan dan intervensi yang lebih tepat sasaran dalam meningkatkan kesejahteraan remaja Gay melalui pengembangan konsep diri dan dukungan sosial yang lebih baik.